PELATIHAN PRODUKSI TELUR ASIN ASAP SEBAGAI UPAYA MENINGKATKAN NILAI JUAL TELUR BEBEK - Liza Aulika; Ari Dewi Cahyati; Ainur Rofieq (Universitas Islam 45 Bekasi, 2022)
Pulo Kaum is one of the remote hamlets within the administrative scope of Kutagandok Village, Kutawaluya District, Karawang Regency, West Java. Unexpectedly, it turns out that this remote village in the middle of a hug rice field, there is potential of all fields. there are several duck breeders who produce boiled salted eggs and are produced in a traditional way with the amount of production not being too large. Since marketing is limited due to many similar industries in a single village as well as in a sub-region, almost every sub-region also has salted egg production communities. because duck eggs have a relatively cheap selling value here, it is necessary to do smoking to increase the selling value of the duck eggs and of course this process can also help the duck eggs to be durable. The purpose of this activity is to increase the selling value of duck eggs, and of course this process can also contribute to the durability of ducks eggs. The aim of this activity is to increase the sales value of duck eggs and to produce sustainable duck eggs using the smoking method. The operation will take place from August to September 2022 in Pulo Kaum Hamlet, Kutagandok Village, Kutawaluya District, Karawang Regency, West Java. The method of carrying out the activity consists of counseling, training and mentoring the residents of Pulo Kaum Hamlet, especially the housewives. The result of this program is an increase in sales value and income from the sale of smoked salted eggs, as well as the creation of smoked salted eggs with a longer shelf life. The conclusion of this program is that producing more and more duck eggs can further increase profits.